Performance analysis of a dual loop thermally regenerative electrochemical cycle for waste heat recovery. (15th July 2016) - Long, Rui; Li, Baode; Liu, Zhichun; Liu, Wei
Abstract: A DLTREC (dual loop thermally regenerative electrochemical cycle) system consisting of two hot electrochemical cells and a cold one is proposed for harvesting waste heat in a more efficient manner. With the maximum power output as the objective function, an optimal analysis of the DLTREC system based on a GA (genetic algorithm) method was conducted for different inlet temperatures of the heat source. For comparison, an optimization analysis of conventional TREC (thermally regenerative electrochemical cycle) systems was also conducted under equivalent criterion. The maximum output, the corresponding electrical and exergy efficiencies, and exergy destruction of the two energy harvesting systems were analyzed and compared. Results revealed that the DLTREC system can increase the power output and decrease the irreversibility. For the prescribed heat source inlet temperature of 393.15 K, the maximum power output of the DLTREC system was 50.11% larger than that of the conventional TREC system and the electrical efficiency was improved by 13.31%. The exergy efficiency of the DLTREC system was 19.41% larger than that of a conventional TREC system. Highlights: A dual loop thermally regenerative electrochemical cycle (DLTREC) is proposed. The performance of DLTREC and conventional TREC is analyzed and compared. DLTREC system can increase the power output and decrease the irreversibility. Maximum power output of the DLTREC is 50.11% larger than that of the conventional TREC.